The Class of Social Capital: A Case Study in Barpak Village Coping and Recovering Process after the Gorkha Earthquake 2015 - Devkota, Narayani (Interdisciplinary Journal of Management and Social Sciences, 2021)
Social capital is one most important attribution of a resilient community. It is manifested in a human relationship or network between the community member such as family, friends, relatives, neighbourhood, membership on a formal and informal group of society, colleague and so on. This article is about the role of Social Capital to cope at the time of Gorkha Earthquake 2015 in  Barpak Village. The article is based on the primary data, which is collected through the interview with 28 ordinary people and a leader of Barpak Village after the Gorkha Earthquake 2015.In this article, I focused on a few key areas of social capital such as family, friendship and neighbourhood, people's involvement in the local level institution, job pattern or profession of a villager, social norm and value as responsibility for fellow community member, collective mobilization in the aftermath of the earthquake. In the Course of my research I found the reality that social capital also closely tied with economic capital. In the rescue and relief time social capital work for all villagers or community members. But when villagers started to rebuild their house, economic capital became a core of social capital.